PAPULES CAUSED BY DERMAL INFILTRATE. Lichen. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2018)
LICHEN. In this heading we treat lichen striatus, which is the most frequent form in childhood, lichen sclerosus and the less frequent forms such as lichen ruber planus, which is rare at this age, lichen actinicus and lichen nitidus. The etiology, symptoms and clinical course of these disorders are very different, in spite of the same name. This is strange only for people who forget that a century ago almost all dermatological disorders were included under the headings of syphilis, lepra and scabies. (...).